Pelaksanaan Scaffolding untuk Mengatasi Kesulitan Siswa dalam Menyelesaikan Masalah PtLSV - Pradina Parameswari; Tjang Daniel Chandra; Susiswo Susiswo (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2018)
Abstract: The activity of finding answers to mathematics problems is not easy. Most of MTs Attaraqqie Malang’s students have difficulties when solve PtLSV problems. Students can’t transform narrative texts to mathematics sentence so that they are hard to find the right answer. Therefore, the researchers do a study that aims to describe the form of student difficulties in solving PtLSV problems and the implementation of scaffolding. This research is a qualitative-descriptive research. The research was conducted in MTs Attaraqqie Malang which was attended by 28 students of class VII. The PtLSV problem is given as many as three items. Three research subjects were selected from diagnostic tests, interviews, and mathematics teacher suggestions. The results showed that students: (1) difficulty of understanding the problem (can’t write down the information that was known and asked the question correctly) so assisted by scaffolding level 2 explaining and reviewing; (2) difficulty of devising a plan (can not determine the initial step and the right concept in solving the problem) and assisted by scaffolding level 1 environmental provision and level 2 reviewing; (3) difficulty of carrying out the plan (unable writing mathematical model according to the problem, not using the correct concept, and can not do systematic calculation so that the final result obtained is wrong) and assisted by scaffolding level 2 that is reviewing and restructuring and level 3 is developing conceptual thinking; (4) difficulty of looking back (not checking the truth of answers and difficult to interpreting answers) and assisted by scaffolding level 2 reviewing and level 3 developing conceptual thinking.Abstrak: Kegiatan menemukan jawaban dari permasalahan matematika tidaklah mudah. Sebagian besar siswa MTs Attaraqqie Malang kesulitan ketika menyelesaikan masalah PtLSV. Siswa tidak dapat mengubah teks naratif ke bentuk kalimat matematika sehingga mereka kesulitan untuk menemukan jawaban benar. Oleh sebab itu, peneliti melakukan penelitian yang bertujuan untuk mendeskripsikan bentuk kesulitan siswa dalam menyelesaikan masalah PtLSV dan pelaksanaan scaffoldingnya. Penelitian ini adalah penelitian kualitatif-deskriptif. Penelitian dilaksanakan di MTs Attaraqqie Malang yang diikuti oleh 28 siswa kelas VII. Masalah PtLSV diberikan sebanyak tiga item. Tiga subjek penelitian dipilih dari tes diagnostik, wawancara, dan saran guru matematika. Hasil penelitian menunjukkan bahwa siswa (1) kesulitan memahami masalah (tidak dapat menuliskan informasi yang diketahui dan yang ditanyakan pada soal dengan benar) sehingga dibantu dengan scaffolding level 2 yaitu explaining dan reviewing; (2) kesulitan menyusun rencana (tidak dapat menentukan langkah awal dan konsep yang tepat dalam menyelesaikan masalah) dan dibantu dengan scaffolding level 1 environmental provision dan level 2 reviewing; (3) kesulitan melaksanakan rencana (tidak menuliskan model matematika yang sesuai masalah, tidak menggunakan konsep yang benar, dan tidak dapat melakukan perhitungan yang sistematis sehingga hasil akhir yang diperoleh salah) sehingga diatasi dengan scaffolding level 2, yaitu reviewing dan restructuring serta level 3, yaitu developing conceptual thinking; (4) kesulitan memeriksa kembali (tidak mengecek kebenaran jawaban dan kesulitan menginterpretasi jawaban) dibantu dengan scaffolding level 2 reviewing dan level 3 yaitu developing conceptual thinking.